2021
DOI: 10.1177/03635465211016008
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Adding a Large Dose of Shoulder Strengthening to Current Nonoperative Care for Subacromial Impingement: A Pragmatic, Double-Blind Randomized Controlled Trial (SExSI Trial)

Abstract: Background: A strong recommendation against subacromial decompression surgery was issued in 2019. This leaves nonoperative care as the only treatment option, but recent studies suggest that the dose of strengthening exercise is not sufficient in current nonoperative care. At this point, it is unknown if adding more strengthening to current nonoperative care is of clinical value. Purpose: To assess the effectiveness of adding a large dose of shoulder strengthening to current nonoperative care for subacromial im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 37 publications
(55 reference statements)
1
35
0
1
Order By: Relevance
“…Our findings, although non-significant, regarding the between-group difference in muscle strength in favour of HEAVY (scaption 10.4%, external rotation 12%) and the trend in less positive clinical tests (an indirect measure of muscle-tendon stiffness) may explain some of the effect of HEAVY on self-reported shoulder function and decreased physical symptoms. However, considering that several studies on shoulder pain-related conditions have failed to show superiority of progressive high-load strengthening exercise could indicate that other factors than the physical response to load are important 19 69 70. Other factors may include the different types of exercise used in HEAVY and LIGHT (eg, full range or not) and the benefits of supervised and individually graded exercise to restore the ability of daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings, although non-significant, regarding the between-group difference in muscle strength in favour of HEAVY (scaption 10.4%, external rotation 12%) and the trend in less positive clinical tests (an indirect measure of muscle-tendon stiffness) may explain some of the effect of HEAVY on self-reported shoulder function and decreased physical symptoms. However, considering that several studies on shoulder pain-related conditions have failed to show superiority of progressive high-load strengthening exercise could indicate that other factors than the physical response to load are important 19 69 70. Other factors may include the different types of exercise used in HEAVY and LIGHT (eg, full range or not) and the benefits of supervised and individually graded exercise to restore the ability of daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why most of our participants presented mild to moderate pain intensity. Participants in our study presented lower pain or function scores compared with those from previous full trials 8 10 65 66. For the full trial, we plan to adopt a multimodal recruitment strategy, including general practice clinics, social media and waiting list from local hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Best evidence recommends exercise therapy be prescribed for patients with shoulder subacromial pain 7 8. However, the strength of evidence supporting this recommendation is limited and findings from two large trials found exercise therapy did not provide additional benefit over usual care 9 10. On the other hand, a recent systematic review and network meta-analysis suggested that, among other interventions, exercise and manual therapy are likely to be effective in the short term for pain and function outcomes 11.…”
Section: Introductionmentioning
confidence: 99%
“…Because this issue relates to external validity it is important—but it is especially important if the trial findings have major implications for current clinical practice. Please see Clausen et al 58 for an example of how the number of potentially eligible participants can be incorporated into the trial flow chart. Please also see the rapid responses 59 to the FIMPACT 60 trial for a discussion of the importance of including the number of potentially eligible participants when trial findings have great implications for clinical practice.…”
Section: Writing Your Trial Reportmentioning
confidence: 99%